Knowledge and attitude regarding legal and ethical aspects in nursing among nurses in a tertiary care teaching hospital, Nepal - Rimal, Himala (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Health care laws and ethics serve as a hallmark in maintaining the equilibrium in the delivery of health care services. The study aimed to find out the knowledge and attitude regarding the legal and ethical aspects of nursing.Method: A cross-sectional study was conducted in Patan Hospital, Patan Academy of Health Sciences, Nepal, from July to August 2017. A self-administered structured questionnaire was used to find out knowledge and attitude regarding legal and ethical aspects in nursing and relation to the demographics- age, an academic qualification in nursing, year of experiences, designation, and place of work in different departments of the hospital. Ethical approval was obtained. Data were analyzed using SPSS, Chi-square test, and the Pearson correlation coefficient was used to determine the association.Result: Findings revealed that among 200 nurses, 26.0% had good knowledge (score >75%), 62.0% average knowledge (score 50%-75%) and 12.0% poor knowledge (score 50%) while 35.5% had an unfavourable attitude on legal and ethical aspects. Knowledge and attitude had no statistically significant association with demographic variables.Conclusion: Most of the nurses had an average level of knowledge and more than half of them had a favourable attitude regarding legal and ethical aspects of nursing.